Collateral Damage in the Human Gut Microbiome - Blastocystis Is Significantly Less Prevalent in an Antibiotic-Treated Adult Population Compared to Non-Antibiotic Treated Controls - Jeffery, Ian B.; Cotter, Paul D.; Scanlan, Pauline D. (Frontiers in Cellular and Infection Microbiology, 2022)
Antibiotics can drive the rapid loss of non-target, phylogenetically diverse microorganisms that inhabit the human gut. This so-called “collateral damage” has myriad consequences for host health and antibiotic mediated changes to the gut microbiota have been implicated in the aetiology of many chronic diseases. To date, studies have largely focused on how antibiotics affect the bacterial fraction of the gut microbiome and their impact on non-bacterial members, including prevalent eukaryal species, such as Blastocystis, remains largely unknown. Here we assessed the prevalence and diversity of Blastocystis in an elderly adult group that were in receipt of antibiotics (n = 86) and an equivalent non-antibiotic treated group (n = 88) using a PCR-based approach. This analysis revealed that although similar subtypes were present in both groups, Blastocystis was significantly less prevalent in the antibiotic-treated group (16%) compared to non-antibiotic treated controls (55%); Fisher’s Exact test, p < 0.0001). Given that antibiotics target structures and molecules of prokaryotic cells to kill or inhibit bacterial populations, the most likely explanation for differences in prevalence between both groups is due to secondary extinctions owing to the potential dependence of Blastocystis on bacteria present in the gut microbiome that were negatively affected by antibiotic treatment. Although further work is required to explore this hypothesis in greater detail, these data clearly show that Blastocystis prevalence in human populations is negatively associated with antibiotic treatment. This finding may be relevant to explaining patterns of variation for this microorganism in different human populations and cohorts of interest.